2017
DOI: 10.1111/ajt.14353
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept Combined With Transient Calcineurin Inhibitor Therapy Prevents Rejection and Promotes Improved Long-Term Renal Allograft Function

Abstract: Belatacept, a T cell costimulation-blocker demonstrated superior renal function, lower cardiovascular risk, and improved graft/patient survival in renal transplant recipients. Despite the potential benefits, adoption of belatacept has been limited in part due to concerns regarding higher rates and grades of acute rejection in clinical trials. Since July 2011 we have utilized belatacept-based immunosuppression regimens in clinical practice. In this retrospective analysis of 745 patients undergoing renal transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 26 publications
6
105
0
Order By: Relevance
“…Patient survival within 12 months after transplant (A) was similar in both groups: death rate in BELACOR group was 0% [0%-7.25%] and in the control group 6.78% [2.88%-15.52%] (P = .07). This result highlights the potential interest already published of an immunosuppressive strategy combining CNIs and belatacept early after transplant (9 months), the high-risk period of acute TCMR, or switching CNIs to belatacept 6 months to 1 year after transplant in order to limit the incidence of T cell-mediated immune events in sensitized recipients and the development of dnDSAs 27. In low-immunological risk kidney allograft recipients, dnDSA incidence is up to 15% within 5 years.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Patient survival within 12 months after transplant (A) was similar in both groups: death rate in BELACOR group was 0% [0%-7.25%] and in the control group 6.78% [2.88%-15.52%] (P = .07). This result highlights the potential interest already published of an immunosuppressive strategy combining CNIs and belatacept early after transplant (9 months), the high-risk period of acute TCMR, or switching CNIs to belatacept 6 months to 1 year after transplant in order to limit the incidence of T cell-mediated immune events in sensitized recipients and the development of dnDSAs 27. In low-immunological risk kidney allograft recipients, dnDSA incidence is up to 15% within 5 years.…”
mentioning
confidence: 67%
“…26 This result highlights the potential interest already published of an immunosuppressive strategy combining CNIs and belatacept early after transplant (9 months), the high-risk period of acute TCMR, or switching CNIs to belatacept 6 months to 1 year after transplant in order to limit the incidence of T cell-mediated immune events in sensitized recipients and the development of dnDSAs. 27 The next remarkable finding was related to the different SAE profile observed in the 2 groups. Patients from the BELACOR group exhibited significantly less infection excluding kidney allograft pyelonephritis and less cardiovascular disorder.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One center has recently detailed the evolution of their belatacept use, with their ultimate strategy of belatacept plus transient CNI maintenance yielding a 1 year rejection rate of 16%, decreased from 50.5% upon their initial implementation. 27 When further evaluating the type and grade of rejections seen in our study, it is interesting that there were no AMR episodes in belatacept recipients compared to two episodes in tacrolimus recipients. Belatacept's role in preventing DSA formation has been previously reported, and this effect was maintained in the small study group even when combined with alemtuzumab induction.…”
Section: Evidence Of Resolving Moderate Pathologic Changes Is Encouramentioning
confidence: 73%
“…A few studies have previously reported the outcomes of depleting induction in conjunction with belatacept; however, these have been conducted in patients receiving more optimal quality donor kidneys. 19,27,28 While we did not seek to evaluate infectious outcomes, we did have two belatacept-treated patients who had biopsy findings of polyomavirus-associated nephropathy in conjunction with ACR. [24][25][26] Similar to previous literature, belatacept recipients experienced higher grades of rejections, but this did not contribute to short-term graft loss, except in one patient, in whom there were adherence concerns.…”
Section: Discussionmentioning
confidence: 99%